A new method to improve indoor environment: Combining the living wall with air-conditioning. (15th May 2022) - Meng, Xi; Yan, Lianyu; Liu, Fudan
Abstract: Indoor plants can improve indoor thermal environment, relieve the anxiety, and reduce the CO2 concentration especially in enclosed rooms with air-conditioning and heating. However, owing to the space limitation and the light requirement, it is very difficult to maintain traditional large-scale plantings indoors. To improve indoor planting efficiency and thermal environment, the living wall was introduced to be combined with air-conditioning. Two identical rooms were built to analyze the efficiency of combining a living wall with air-conditioning. One room contained a living wall and air-conditioning, while the other room only with air-conditioning was served as a reference. The indoor thermal environment and CO2 concentration were monitored, while the 64 participants were questioned to display their subjective feelings in two rooms. The results showed that combining the living wall lowered the relative humidity by 2.6%, maintained the indoor air speed at 0.20 m/s∼0.30 m/s and reduced the CO2 concentration by approximately 10%, while it increased the uniformity of these environmental parameters. The average skin temperature in the room with the living wall was 0.2 °C higher than that in the referred room and closer to the neutral mean skin temperature. The living wall significantly improved the subjective evaluation on indoor environment, especially in air movement and air freshness, with the thermal comfort level from 0.13 (Slightly higher than ''Neutral (0)'') to 0.73 (Slightly lower than ''Comfortable (+1)''). Highlights: A new method was proposed to improve indoor environment. Living wall reduced indoor CO2 concentration by about 10%. Living wall also could reduce indoor relative humidity. Living wall could improve indoor thermal comfort.